MENINGKATKAN KETERAMPILAN BERBELANJA SISWA TUNAGRAHITA DENGAN MEDIA GAMBAR - Rifqi Syahrul Azizah; Imanuel Hitipeuw; Abdul Huda (Universitas Negeri Malang, 2014)
The purposes of this research was to increase the shopping skills of a student with intellectual disability in SLB Kemala Bhayangkari Trenggalek by using pictures media evaluated based on three aspects: (1) the ability of shoping in minimarket, (2) the ability of items purchasing and (3) the ability of expensive and cheap concepts. The research method was Single Subject Research (SSR) appoarch, reversal design ABAB. The subject was a sixth grade student with intellectual disaility in SLB Kemala Bhayangkari Trenggalek. The student classified into a mild or intermitten intellectual disability. Data collecting of both shopping ability and the ability of items purchasing was done through observation, and the ability of expensive and cheap concepts was collected by the results of a written test. The analysis of this research was by visual analysis graph. The results of the shopping skill analysis were based on three aspects: (1) the ability of shopping in minimarket, (2) the ability of items purchasing and (3) the ability of expensive and cheap concepts were increasing after being given the intervention. From the results of the graph showing the mean, level and trend were increasing from baseline to intervention. Latency analysis also showed that the changes in behavior occured was less likely to take long time over the intervention. Total Mean of over all aspects in baseline 1 (A1) phase was 22,3, then the mean increasing in intervention 1 (B1) phase was 58,3, the mean total of baseline 2 (A2) phase was 39,5 and the intervention 2 (B2) was 63,5. Tujuan dari penelitian ini adalah untuk meningkatkan kemampuan belanja dari siswa dengan cacat intelektual di SLB Kemala Bhayangkari Trenggalek dengan menggunakan media gambar dievaluasi berdasarkan tiga aspek: (1) kemampuan belanja di minimarket, (2) kemampuan item pembelian dan (3) kemampuan konsep mahal dan murah. Penelitian ini merupakan Subjek Tunggal Desain (SSD). Untuk mendapatkan data, peneliti menggunakan tiga instrumen: pengamatan dan hasil test.The tertulis dari analisis keterampilan belanja didasarkan pada tiga aspek: (1) kemampuan belanja di minimarket, (2) kemampuan item pembelian dan (3 ) kemampuan konsep mahal dan murah yang meningkat setelah diberi intervensi. Dari hasil grafik yang menunjukkan rata-rata, tingkat dan tren yang meningkat dari awal sampai intervensi. Analisis Latency juga menunjukkan bahwa perubahan perilaku terjadi kurang mungkin untuk mengambil waktu yang lama selama intervensi. Total rata-rata lebih dari semua aspek di awal 1 (A1) fase adalah 22,3, maka berarti meningkatnya intervensi 1 (B1) fase adalah 58,3, total rata-rata dasar 2 (A2) fase adalah 39,5 dan intervensi 2 (B2) adalah 63,5.